(untitled) (Education in the 21st Century, 2025)
This study empirically examined the proficiency levels of History students at Yerevan State University (YSU) in Critical Historical Thinking Competence (CHTC) and Digital-Historical Literacy (DHL). The research addresses the limited availability of empirical assessments of historical-thinking competencies and examines a local institutional challenge at YSU — the integration of externally produced academic research into teaching practice — through measurable indicators of critical-historical and digital-historical literacy. A Convergent Parallel Mixed Methods design was employed, involving a quantitative cohort of 150 students (N=150) and a qualitative cohort of 20 participants (N=20). Data were collected using performance-based CHTC assessments and a customized Digital-Historical Literacy Scale (D-HiLS), augmented by semi-structured interviews. Quantitative analysis revealed that undergraduate students (n = 97) scored lower on argumentative synthesis tasks (M = 2.73, SD = 1.24) compared to graduate students (n = 53; M = 3.68, SD = 0.92), t≈4.8, p<.001, d≈0.8, p = .036, Cohen’s d = .41. This result suggests that the ability to integrate divergent historical perspectives improves with advanced academic experience but remains below the level reported in comparable European studies. The difference between self-reported confidence (M = 7.8, SD = 1.2) and observed performance in digital source evaluation (M = 3.6, SD = 1.4) was statistically significant, t(148) = 6.03, p < .001, d = .69, revealing an evident overconfidence effect. Qualitative interviews confirmed that the gap is rooted not only in methodological rigidity but also in limited access to international digital archives and a lack of structured training in digital-source verification.